1996
DOI: 10.1097/00005537-199603000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Laser Photochemotherapy With Anthracyclines on Cultured Human Squamous Carcinoma Cells

Abstract: A new treatment for cancer has been tested in vitro using light-sensitive anthracyclines followed by laser photoactivation, as described by several investigators. We previously reported 10-fold enhanced laser killing after 2 hours of incubation with daunomycin by cultured human carcinoma cells. This short-term uptake leads to drug localization in cytoplasmic and membrane sites prior to nuclear accumulation and topoisomerase inhibition. In the present study, daunomycin was incubated for 2 or 24 hours with P3 sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
(39 reference statements)
1
17
0
Order By: Relevance
“…The current studies corroborate and extend previous in vitro experiments that demonstrate that anthracyclines have dual properties as photodynamic agents and as cytostatic anticancer drugs [1,8,[16][17][18][19]. For example, a recent in vitro study with Adriamycin using explanted human squamous-cell carcinoma showed that exposure to the argon laser at 514 nm led to over 50% increased cytotoxicity at drug levels equal to or above 5 g/ml compared to chemotherapy alone in the dark [19].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The current studies corroborate and extend previous in vitro experiments that demonstrate that anthracyclines have dual properties as photodynamic agents and as cytostatic anticancer drugs [1,8,[16][17][18][19]. For example, a recent in vitro study with Adriamycin using explanted human squamous-cell carcinoma showed that exposure to the argon laser at 514 nm led to over 50% increased cytotoxicity at drug levels equal to or above 5 g/ml compared to chemotherapy alone in the dark [19].…”
Section: Discussionsupporting
confidence: 87%
“…Combining intratumor chemotherapy with laser energy delivery via interstitial fiberoptics should be most effective using drugs activated by photothermal energy [1][2][3]. Adriamycin derivatives are the most common anticancer agents that interact with light to elicit fluorescence, membrane photolabeling, laser activation, and killing of tumor cells [1,4,5] Imaging-guided minimally invasive surgery is a new concept that uses ultrasound and/or high-speed magnetic resonance imaging to guide various energy sources such as lasers, radio frequency, ultrasonic, or cryotherapy devices for treatment of deep-seated tumors and monitoring of tissue changes during energy depositon [6]. Unlike open surgical procedures in which there is direct visual control of the field, percutaneous techniques require imaging modalities to define the anatomy of adjacent neurovascular structures while providing precise guidance for minimally invasive access to tumors and continuous monitoring of the tissue ablation process.…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is an approach which has a wide range of application from acne to wrinkles, bactericidal cleansing, cancer treatment, etc (D'Cruz et al, 2004). In PDT, the absorption of photons by organic compounds can excite orbital electrons and increase kinetic energy levels leading to chemical reactions, but also may include light emission as fluorescence or transfer energy directly to oxygen molecules forming singlet and free radical species (Carmichael et al, 1983;Paiva et al, 1996). Anthracyline derivatives, such as adriamycin and daunomycin, are the most common anticancer agents that interact with light to elicit fluorescence, membrane photo labeling, laser activation and killing of tumor cells (Andreoni et al, 1991;Nahabedian et al, 1988;Saxton et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown that yeast cells were sensitized and killed by adriamycin after irradiation at 365nm, a wavelength that presented no effect in the absence of the drug. Also, cytotoxicity of several anthracycline derivatives are significantly enhanced by continuous wave green light of argon (514nm) or KTP (532nm) laser illumination of different types of cancer, both in vitro (Li and Chignell, 1987;Paiva et al, 1996) and in vivo. (Nahabedian et al, 1988;Peavy et al, 1992;Soudant et al, 1992;Paiva et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…TMPyP has been shown to be a very versatile and effective photosensitizer, for its considerable photobiological activity against tumor cells [13], Gram positive and Gram negative bacteria [14,15], protozoa [16], and viruses [17]. On the other hand, ADM possesses dual properties, as cytostatic agent whose activity include intercalation with DNA [18] and bioreductive activation leading to the formation of drug semiquinone and oxygen free radicals [19,20], and as a photodynamic agent when photoactivated by non-thermal irradiation [21,22]. Such facts rendered it worthy to evaluate the efficacy of both TMPyP and ADM as a combined photochemotherapeutic modality against tumor cells.…”
Section: Introductionmentioning
confidence: 99%